Reaction Kinetics in the Production of Pd Nanoparticles in Reverse Microemulsions: Effect on Particle Size - Sánchez Morales, Jhon Freddy (2018)
In the synthesis of metallic nanoparticles in microemulsions, we hypothesized that particle size is mainly controlled by the reaction rate. Thus, the changes observed on the particle sizes as reaction conditions, such as concentrations, temperature, type of surfactant used, etc., are varied should not be correlated directly to the modification of those conditions but indirectly to the changes they produce on the reaction rates. By means of time resolved UV-vis spectroscopy, we measured the reaction rates in the production of Pd nanoparticles inside microemulsions at different reactant concentrations, keeping all the other parameters constant. The measured reaction rates were then correlated with the particle sizes measured by transmission electron microscopy (TEM). We found that nanoparticle size increases linearly as the reaction rates increases, independently of the actual reactant concentrations. We proposed that the kinetics is controlled mainly by the diffusion of the reducing agent through the surfactant monolayer covering the microemulsion membrane. With this model, we predicted that particle size should depend indirectly, via the reaction kinetics, on the micelle radius (v0 ~ r^-3), the water volume (v0~vw^3) and the total microemulsion volume (v0~vT^-3), and temperature (Arrhenius). Some of these predictions were explored in this article.